Role of antibiotics in elective clean surgeries: limiting its use to single shot preoperative dose - Jamdade, P. T.; Chawada, Meghraj J.; Samant, Apurva (International Surgery Journal, 2020)
Background: Conventional antibiotic therapy during operation not only increases the financial burden on patient, not only increases chances of adverse reactions among them but also not effective in reducing the infection rate after surgery. Single dose prophylactic antibiotic or maximum 24 hours dosing during or before surgery was found to be equally effective. Objective was the to study utility of single shot antibiotic prophylaxis in patients undergoing surgery Methods: This prospective study includes 100 clean elective surgical cases randomized to groups of 50 each. Single dose prophylactic antibiotic was given to cases in the study group and conventional antibiotic therapy was given to cases in the control group. Study group cases received Injection Ceftriaxone in the dose of 2 gm intravenously. This was given at induction or half an hour before the incision was given. Second dose was given if there was delay in starting the surgery for more than three hours. Dose of the antibiotic was adjusted for children, underweight and obese persons. For cases in the control group. Injection ceftriaxone 1 gm was given intravenously twice a day for three days. Surgical site infection incidence was recorded. Results: Both the groups were comparable for age, sex, diagnosis and hence the type of surgery performed. The incidence of fever, redness, swelling and wound discharge which are the signs of surgical site infection after surgery was not found to be statistically significantly different. Management protocol was also not significantly different after the surgery. Conclusions: Single shot antibiotic before surgery is equally effective in reducing the incidence of surgical site infections (SSIs) compared to conventional antibiotic therapy.